(untitled) (CIPEEX, 2025)
Pet+ is an innovative platform designed to address the growing needs of the pet market by serving both businesses and pet owners. The platform provides a diverse range of services, including pet grooming, veterinary care, and access to stores offering pet-related products such as food, toys, medications, and accessories. The motivation behind Pet+ is to simplify the daily lives of pet owners and small-to-medium-sized businesses catering to this market. The platform solves a recurring issue: the difficulty in finding and scheduling essential services like grooming and veterinary care while streamlining the purchase of specific pet products. By centralizing all these needs into a single integrated solution, Pet+ enhances user convenience and contributes to the development of the pet market. This initiative strengthens the connection between businesses and a growing, demanding audience, providing an efficient and practical experience for all users.